Coastal water circulation patterns around the Northern Channel Islands and Point Conception, California. (November 2015) - Fewings, Melanie R.; Washburn, Libe; Ohlmann, J. Carter
Graphical abstract: Highlights: Mean cross-shelf flow profiles near the 15-m isobath are similar at most of 21 sites. Wind predicts water velocity at few sites, and EOF 1 captures only ∼25% of variance. The flushing time of the shelf onshore of the 15-m isobath is short, ∼1–2 days. These sites should display inner-shelf, not mid-shelf, dynamics >50% of the time. Near many kelp beds, mean Eulerian flow is onshore (offshore) at mid-depth (bottom). Abstract: The Northern Channel Islands in California host multiple Marine Protected Areas containing kelp forest ecosystems. Little is known about the water circulation onshore of the 20-m isobath. We use water velocity recorded at 21 sites near the 15-m isobath at the Islands and mainland during 1999–2012 to describe the water circulation on time scales of days to months. The mean circulation is eastward or weak at the Islands but poleward along the mainland (speeds 0–10 cm s −1 ). The subinertial-frequency along-shelf flow is surface-intensified and reverses direction on time scales of days. In summer, the flow becomes more poleward throughout the region. The mean cross-shelf flow profiles are strikingly similar at most sites, with flow speeds 1–2 cm s −1 . The mean flow near bottom in the vicinity of the kelp forests is offshore. The time-varying, two-layered response to wind is stronger, up to 6 cm s −1 . The flushing time of the shelf onshore of the 15-m isobath is short, at most ∼2 dy. At a few sites exposed to the prevailing wind, up to 60% of the velocity variance is predictable from wind measured in the Santa Barbara Channel. In the lee of Point Conception or at the Islands, however, regional wind explains little of the velocity variance. During weak winds, the velocity at some mainland, but not Island, sites responds to pressure gradients measured along the mainland coast. These pressure gradients are associated with local wind relaxations at Pt. Conception, not with remotely-generated coastal-trapped waves.